The Saving Behavior of Heterogeneous Households and Credit Constraints: A Decomposition - Aljahani, Maryam (Journal of Applied Business and Economics, 2022)
This paper sheds light on how saving decisions respond to credit constraints. In this paper, we examine the role credit constraints play in the savings decisions of households by focusing on a well-defined set of reasons for their savings. To do so, we classify the saving motives as precautionary saving, saving to finance investments, and saving for retirement. We find that credit-constrained households are less likely to save for retirement and liquidity, while they are more likely to save for investment purposes. Constrained Black households are more likely to save for in- vestment purposes. Discouraged households are more likely to save for investment and less likely to save for retirement purposes. When households are credit-constrained, they use their savings to smooth their consumption rather than to accumulate wealth over time.